The Role of Kapitan Telukabessy in the Kapahaha War (1973-1946) in Morella Village, Leihitu District, Central Maluku Regency - Sumira Malawat; Fitria Wajo; Saly Behuku; Sem Touwe; Johan Pattiasina (Universitas Syiah Kuala, 2022)
This study aims to reveal the background of the Kapahaha War (1637 1646), explain the role of Kapitan Telukabessy in the conflict, and analyze its impact on the people of Morella Village, Leihitu District, Central Maluku Regency. Kapitan Telukabessy was a charismatic and courageous leader who led the resistance of the Morella community against Dutch colonial forces from the steep and strategic Kapahaha Hill. Using historical research methods, the study found that Telukabessy's nine-year struggle had a significant influence on shaping the collective identity and historical awareness of the Morella people. To this day, his contributions are honored and remembered, as seen in the naming of public spaces such as Telukabessy Street in Ambon City. His legacy stands as a symbol of resistance and remains deeply rooted in the collective memory of the Ambonese community